Adaptive learning systems in mathematics education: An integrated bibliometric mapping and systematic literature review - Suci Nurhayati; Sudirman Sudirman; Kartono Kartono; Camilo Andrés Rodríguez-Nieto (KALAMATIKA Jurnal Pendidikan Matematika, 2026)
Research on adaptive learning systems (ALS) in mathematics education has increased substantially in recent years; however, existing studies remain fragmented across system types, educational levels, and implementation contexts. Most prior reviews have focused either on technological characteristics or learning outcomes, providing limited insight into how adaptive learning systems are systematically implemented and synthesized within mathematics education. Addressing this gap, this study examines adaptive learning systems in mathematics education through an integrated bibliometric mapping and systematic literature review. A systematic literature review was conducted and reported in accordance with PRISMA guidelines to identify, screen, and select relevant studies from major academic databases. Bibliometric mapping analysis using VOSviewer was then employed to explore publication trends, keyword co-occurrence, and thematic structures within the selected literature. The findings indicate that adaptive learning systems generally contribute positively to mathematics learning outcomes; however, their effectiveness is closely associated with pedagogical integration and teacher preparedness rather than technological sophistication alone. A phased implementation pattern is observed, beginning with teacher-led enhancement approaches and progressing toward more technology-mediated models. While AI-based systems demonstrate strong potential, moderately complex adaptive systems appear more feasible for institutions with limited resources. These findings highlight the importance of pedagogical readiness in the adoption of adaptive learning systems and suggest directions for future research, particularly in underrepresented educational levels.